Advances and Reflection on the Application of Digital Storytelling in Hospice Care - Jiahui LIU; Mengjie LIU (Yixue yu zhexue, 2025)
This paper systematically combs the application status and practical experience of digital storytelling in the field of hospice care, and provides theoretical reference for innovative practice in this field in China. Digital stories provide multi-dimensional humanistic support for patients, bereaved families and nursing students in multiple forms such as life documentary, digital heritage inheritance and educational visualization. From a practical perspective, China's hospice digital storytelling has advantages such as market demand-driven, policy support, and international experience, but they face realistic challenges such as lack of professionals, inadequate privacy protection mechanism, inconsistent story quality, and limited cultural adaptation. Therefore, it is suggested to train professionals, enrich the production of digital stories, improve the evaluation criteria of stories, and deepen the integration of local cultural elements in order to promote the sustainable development of hospice digital storytelling.